2022
DOI: 10.1093/mnras/stac077
|View full text |Cite
|
Sign up to set email alerts
|

A new measurement of the Hubble constant using fast radio bursts

Abstract: Fast radio bursts (FRBs) are very short and bright transients visible over extragalactic distances. The radio pulse undergoes dispersion caused by free electrons along the line of sight, most of which are associated with the large-scale structure (LSS). The total dispersion measure therefore increases with the line of sight and provides a distance estimate to the source. We present the first measurement of the Hubble constant using the dispersion measure – redshift relation of FRBs with identified host counter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 54 publications
3
32
1
Order By: Relevance
“…Finally, we note that measuring the overall amplitude of the DM(z) relation at high redshifts could, in principle, allow us to constrain other cosmological parameters as well since the amplitude is proportional to the combination H b m 0 0.5 W W -. However, we do not focus on such constraints here because these parameters can be constrained by the low-redshift (z < 5) FRB data to a much greater accuracy (Zhou et al 2014;Hagstotz et al 2022). In summary, a successful high-z FRB survey could substantially advance our understanding of reionization and provide powerful new constraints on cosmological parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that measuring the overall amplitude of the DM(z) relation at high redshifts could, in principle, allow us to constrain other cosmological parameters as well since the amplitude is proportional to the combination H b m 0 0.5 W W -. However, we do not focus on such constraints here because these parameters can be constrained by the low-redshift (z < 5) FRB data to a much greater accuracy (Zhou et al 2014;Hagstotz et al 2022). In summary, a successful high-z FRB survey could substantially advance our understanding of reionization and provide powerful new constraints on cosmological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…For the bulk of the detected FRBs, a large fraction of the DM is due to the free electrons found in the intergalactic medium (IGM; Xu & Han 2015), with a lesser contribution from the FRB host environment and the Milky Way. The evolution of the DM with the cosmological redshift of the FRB source may shed light on the properties of the IGM (Macquart et al 2020) and can be used to measure cosmological parameters (Deng & Zhang 2014;Gao et al 2014;Zhou et al 2014;Yang & Zhang 2016;Walters et al 2018;Jaroszynski 2019;Kumar & Linder 2019;Madhavacheril et al 2019;Walters et al 2019;Wu et al 2020;Hagstotz et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A more ambitious goal is to use the DM-𝑧 relation to measure the proper distance the Universe [183], the equation of state of dark energy [200,158,195,131], Hubble constant [81,58,170], Hubble parameter [168], dark matter [109,166] and the cosmic Helium and hydrogen reionization history [198,194]. This would require at least two conditions.…”
Section: Applications In Cosmologymentioning
confidence: 99%
“…The data of localized FRBs could be used to constrain cosmological parameters with the Macquart relation, which provide a relationship between DM IGM and z [31]. There have been a series of works using FRBs as a cosmological probe to study the expansion history of the universe, such as estimating the cosmological parameters [37] and conducting cosmography [38] by using FRBs and Gamma-Ray Bursts association, using FRBs to measure Hubble parameter H(z) [39] and the Hubble constant [40,41], using the FRB data combined with the BAO data or the type Ia supernovae (SN) data to break the cosmological parameter degeneracies [42,43], using FRB dispersion measures as distance measures [44], probing compact dark matter [45,46], testing Einstein's weak equivalence principle [47][48][49], and many other works [50][51][52][53][54]. For a recent review, see ref.…”
mentioning
confidence: 99%
“…It has been shown that the FRB data could break the parameter degeneracies in the CMB and GW data. But these two models and the most considered models in the literature [37][38][39][40][41][42][43] are parametred and phenomenological models, and thus it is important to consider some dark energy models with deep and solid theoretical foundations and see whether the FRB data are still useful in cosmological parameter estimation in these dark-energy theoretical models. In this work, we investigate two dark energy models, i.e., the holographic dark energy (HDE) model and the Ricci dark energy (RDE) model.…”
mentioning
confidence: 99%